Management of Symptomatic Inguinal Hernia Under Local Anesthesia in Covid Pandemic Our Experience - Zain Ul Abideen Ali, Tahir Hamid, Amir Usman, Sehrish Majeed, Javeria Usman, Fahad Abbas, Mansab Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Health care burden has increased since the pandemic of Covid-19 has emerged. The healthcare resources are limited currently and majority surgeries have been postponed because of the current pandemic. Therefore, the main concern of carrying out any surgery at current point is mainly in those patients that are landing in emergency. Symptomatic inguinal hernia being a common presentation in emergency can be dealt by applying local anesthesia. Objective: To evaluate the outcome (in terms of efficacy and safety) of local anesthesia for managing symptomatic inguinal hernia in a tertiary care hospital during current Covid-19 pandemic. Methodology: It was a descriptive study.60 males were enrolled with inguinal hernia of age 30-60 years. IV line was secured and local anesthesia was administered under aseptic measures. Lichtenstein repair, a mesh technique was applied in all patients for treating the inguinal hernia. Patients were evaluated postoperatively after 2 hours and 6 hours for any complications. Results: Mean age of the patients was 38.2±10.542, Mean time to eat was 3.85 ±3.138. Mean time to ambulate was 4.37 ±2.51. Mean pain score was 5.78± 2.131 postoperatively and after 6 hours it was 2.24 ±0.84. Indirect hernia was present in 74% patients whereas direct hernia was present in 26%. 6.67% patients had nausea/vomiting, 3.3% developed hematoma and 1.67% had wound infection. Conclusion: Local anesthesia is effective in all patients who have to undergo inguinal hernia surgery, in terms of efficacy and safety.